Properties and Processing of Populus deltoides Bartr. For Producing Quality Sawn and Seasoned Timber - Pandey, C. N.; Kambo, A. S. (Indian Forester, 2001)
Plantation grown wood Populus deltoides, though presently available, possess problems in producing standard quality sawn and seasoned timber. Studies on air and conventional kiln drying behaviour revealed that though it is not difficult to dry, the material is prone to severe distortions like bow, crook and honeycombing. The reason for the tendency to warp is predominantly due to juvenile nature of wood and presence of residual growth stress. The major problem of this distortion degrade has been solved by adopting Saw Dry Rip method of sawing and high temperature seasoning. Recent improvements in processing have enabled this species to be commercially used for several value added products such as pencil making, doors and window shutters, light furnitures and for making quality packing cases etc. The details of the sawing and seasoning technology for Poplar are summarized in this paper.